Spatial analysis of COVID-19 and traffic-related air pollution in Los Angeles. (August 2021) - Lipsitt, Jonah; Chan-Golston, Alec M.; Liu, Jonathan; Su, Jason; Zhu, Yifang; Jerrett, Michael
Highlights: Environmental factors such as air pollution may contribute to Covid-19 incidence and death. This study investigates whether air pollution relates to Covid-19 incidence and mortality in neighborhoods of Los Angeles. Los Angeles is a global epicenter for the pandemic with 1, 105, 989 cases to date. Findings suggest that chronic exposure to nitrogen dioxide exerts large effects on Covid-19 disease incidence and mortality. Higher levels of air pollution in neighborhoods with high proportions of Latinx and Black people. Higher pollution may explain why these groups suffered disproportionately from the pandemic.